1996
DOI: 10.1103/physrevb.53.7699
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent specific heat below 1 K in the spin-density-wave state of (TMTSF)2PF6

Abstract: Large time-dependence effects have been measured below 1 K in the specific heat of the spin-density-wave ͑SDW͒ compound ͑TMTSF͒ 2 PF 6 , well below its glass transition temperature at 3.5 K. These effects indicate that most of the low-energy excitations characteristic of the disordered nature of the SDW subsystem are decoupled from the phonon bath for tտ1 s. A comparison is done with the related slow heat release observed over similar long time scales ͑up to 10 4 -10 5 s͒ in structurally disordered materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…It has been proposed that the SDW state of ͑TMTSF͒ 2 PF 6 is divided into three subphases: SDW1 between 12 and 3.5 K, SDW2 between 3.5 and 2 K, and SDW3 below 2 K. 31 In NMR studies, 31,32 two anomalies of T 1 −1 were found at about 3.5 and 2 K besides the SDW transition temperature of 12 K. The corresponding anomalies were observed by heat capacity, 33,34 dielectric constant, 33,35 magnetic susceptibility, 36 and magnetotransport. 37 Recently, Kagoshima et al 12 reported by x-ray measurement that the superlattice reflections due to 2k F and 4k F CDWs disappeared below 3-4 K. They stated that the SDW1 and SDW2 subphases are the coexistent SDW-CDW state, but the amplitude of CDW is very small in the SDW2 subphase.…”
Section: Discussionmentioning
confidence: 96%
“…It has been proposed that the SDW state of ͑TMTSF͒ 2 PF 6 is divided into three subphases: SDW1 between 12 and 3.5 K, SDW2 between 3.5 and 2 K, and SDW3 below 2 K. 31 In NMR studies, 31,32 two anomalies of T 1 −1 were found at about 3.5 and 2 K besides the SDW transition temperature of 12 K. The corresponding anomalies were observed by heat capacity, 33,34 dielectric constant, 33,35 magnetic susceptibility, 36 and magnetotransport. 37 Recently, Kagoshima et al 12 reported by x-ray measurement that the superlattice reflections due to 2k F and 4k F CDWs disappeared below 3-4 K. They stated that the SDW1 and SDW2 subphases are the coexistent SDW-CDW state, but the amplitude of CDW is very small in the SDW2 subphase.…”
Section: Discussionmentioning
confidence: 96%
“…From previous investigations it is known that in insulating magnetic crystals (e.g., the spin ice compound Dy 2 Ti 2 O 7 37 and several low-dimensional quantum magnets 38 ), the slow relaxation of low-energy excitations can introduce some dependence of the measured specific heat on extrinsic parameters, such as, the measurement duration, thermal anchoring of the sample, applied magnetic field, etc. 38,39 . A combination of these factors might be related to the observed orientation dependence of specific heat at low-temperatures.…”
Section: B Magnetic Ordering Temperature Of the Doped Chainsmentioning
confidence: 99%
“…Consequently, we disregard this contribution (and any other from low-energy charge-carrying excitations 20 ). In solids states with three translational and three rotational degrees of freedom, the specific heat contribution from acoustic phonons can be calculated by the Debye model 21 :…”
Section: A Nonlinear Current-voltage Characteristicsmentioning
confidence: 99%